A dual-responsive RhB-doped MOF probe for simultaneous recognition of Cu2+ and Fe3+ - Teng Zhang; Rui Cao; Jingying Li; Hanxiao Tang; Hang Su; Weisheng Feng; Zhijuan Zhang (Scientific Reports, 2024)
Abstract Based on the dual response of RhB@UiO-67 (1:6) to Cu2+ and Fe3+, a proportional fluorescent probe with (I 392 /I 581 ) as the output signal was developed to recognize Cu2+ and Fe3+. Developing highly sensitive and selective trace metal ions probes is crucial to human health and ecological sustainability. In this work, a series of ratio fluorescent probes (RhB@UiO-67) were successfully synthesized using a one-pot method to enable fluorescence sensing of Cu2+ and Fe3+ at low concentrations. The proportional fluorescent probe RhB@UiO-67 (1:6) exhibited simultaneous quenching of Cu2+ and Fe3+, which was found to be of interest. Furthermore, the limits of detection (LODs) for Cu2+ and Fe3+ were determined to be 2.76 μM and 0.76 μM, respectively, for RhB@UiO-67 (1:6). These values were significantly superior to those reported for previous sensors, indicating the probe’s effectiveness in detecting Cu2+ and Fe3+ in an ethanol medium. Additionally, RhB@UiO-67 (1:6) demonstrated exceptional immunity and reproducibility towards Cu2+ and Fe3+. The observed fluorescence quenching of Cu2+ and Fe3+ was primarily attributed to the mechanisms of fluorescence resonance energy transfer (FRET), photoinduced electron transfer (PET), and competitive absorption (CA). This work establishes a valuable foundation for the future study and utilization of Cu2+ and Fe3+ sensing technologies.